2020
DOI: 10.1097/ju.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Prostate Multiparametric Magnetic Resonance Imaging by Using Clinical Parameters to Predict Negative and Indeterminate Findings

Abstract: Purpose: We sought to develop a triage strategy to reduce negative and indeterminate multiparametric magnetic resonance imaging scans in patients at risk for prostate cancer. Materials and Methods: In this retrospective study we evaluated 865 patients with no prior prostate cancer diagnosis who underwent prostate multiparametric magnetic resonance imaging between 2009 and 2017. Age, prostate volume, prostate specific antigen and prostate specific antigen density were assessed as predictors of positive multipar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…In this study, our developed multivariate model including tPSA, fPSA, and PV has a similar diagnostic accuracy with the PSAD in the prediction of suspicious MRI-PCa ( P = 0.108). This was consistent with the study by Dominik Deniffel ( 13 ). Although cross-study comparisons are challenging, our multivariate model (AUC = 0.80) performed similarly with the model developed by Dominik Deniffel (AUC = 0.75) in the prediction of mpMRI results ( 13 ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, our developed multivariate model including tPSA, fPSA, and PV has a similar diagnostic accuracy with the PSAD in the prediction of suspicious MRI-PCa ( P = 0.108). This was consistent with the study by Dominik Deniffel ( 13 ). Although cross-study comparisons are challenging, our multivariate model (AUC = 0.80) performed similarly with the model developed by Dominik Deniffel (AUC = 0.75) in the prediction of mpMRI results ( 13 ).…”
Section: Discussionsupporting
confidence: 94%
“…Studies demonstrated that a risk-based triage strategy could reduce more unnecessary biopsy and the overdiagnosis in comparison with single parameters (8,11,25). However, the study about developing a multivariate model to predict the results of prostate mpMRI and selecting patients who could benefit from mpMRI is limited (13,14). The study by Alberts et al introduced the concept of a patient triage strategy to avoid prostate mpMRI, and assessed the rate of potentially avoidable mpMRI by applying the risk calculators for detecting PCa (Rotterdam Prostate Cancer Risk Calculator, RPCRC) in a small cohort with one or more previously negative random TRUSguided biopsies (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have seen a considerable recent effort to reduce the number of unnecessary prostate biopsies and more accurately diagnose clinically significant prostate cancers (csPCa). 1,2 Multiparametric magnetic resonance imaging (mpMRI) is a promising tool for detecting prostate cancer (PCa), 3 and clinicians are currently using mpMRI as a biopsy decision-making strategy. 4 Whether men with a negative mpMRI, defined as Prostate Imaging Reporting and Data System version 2 (PI-RADS v2) scores of ≤ 2, should undergo prostate biopsy remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%